PROBLEMS IN SPEAKING ENGLISH IN MARITIME FACULTY OF IVET UNIVERSITY - Wibowo, Rahmat Ari (Marine Science and Technology Journal; Vol 5 No 1 (2024): Marine Science and Technology Journal, 2024)
The  main  objective  of  this  research  to  find  out  speaking  problems’ students English at the fifth semester of Ship electrical engineering of Maritime Faculty of Ivet University The method of this research was qualitative descriptive, which describe problems in speaking English by the students, the population of this research was conduct students at the fifth semester of English education department at Ship electrical engineering of Ivet University. A sample of this research was taken by purposive sampling which consisted of 20 statements to 35 students. To get data, the researcher uses questionnaires and class observation. Based on the research findings, the result of the research showed that students problems fluency and accuracy in speaking English. There are inhibition, that consists of students feel shy of being attention when speak English, they cannot remember anything to say and they do not have any motivation to express themselves, worried about making mistakes, afraid of being criticized when speak English incorrect, it is caused by their low understanding in grammar, low vocabullary,  and  low  level  of  pronounciation  mastery.  The next problem is nothing to say, students afraid of being faulted, have no idea to speak English, and lazy to speak English, it is caused by uninteresting topic, and difficult topic